Teori Belajar Operant Conditioning B.F Skinner Menurut Al-Syarqawi Dalam Pendidikan Agama Islam - Lutfiyah; Muhlis, Achmad (Bayani, 2025)
The problem of low student motivation, discipline, and engagement in learning is a major challenge in education. Islamic Religious Education (PAI) plays a crucial role in shaping students' character and behavior in accordance with religious values. In this study, the researcher examines how B.F. Skinner's Operant Conditioning theory is applied in Islamic Religious Education learning. The problem formulation is how the concept of Operant Conditioning theory is applied in PAI, its impact on student behavior, and how this theory can be adapted to suit religious values ??and child protection. The study used a literature review method with descriptive analysis. The results show that positive reinforcement such as praise and rewards are effective in fostering good behavior in accordance with Islamic values. Punishment is still used, but in a way that is not harmful and in accordance with child protection regulations in Indonesia. The main criticism is that this theory does not pay enough att ention to aspects of students' intentions and spiritual values, so a more holistic and child-friendly approach is needed. The advantages of this theory are that it can motivate students through consistent rewards and create a positive and structured learning environment. In conclusion, Operant Conditioning theory remains relevant when combined with local religious and cultural values ??for more meaningful learning and to shape students' overall character. Teachers are advised to use positive reinforcement and punishment wisely for best results.